Longitudinally Extensive Transverse Myelitis with Intramedullary Metastasis of Small-Cell Lung Carcinoma: An Autopsy Case Report - Kenya Nishioka; Ryota Tanaka; Satoshi Tsutsumi; Hideki Shimura; Yutaka Oji; Harumi Saeki; Yukimasa Yasumoto; Masanori Ito; Nobutaka Hattori; Takao Urabe (Case Reports in Neurological Medicine)
Background. Longitudinally extensive transverse myelitis (LETM) is characterized by spinal cord inflammation extending vertically through three or more vertebral segments. The widespread use of MRI revealed LETM more frequency than ever. We report the case of a patient with pathologically confirmed small-cell lung carcinoma metastasis into the spinal cord presenting as LETM. Case Presentation. A 74-year-old man developed rapidly progressive sensorimotor disturbance and vesicorectal dysfunction. T2-weighted magnetic resonance imaging of the spine revealed LETM at the level of from T3 to conus medullaris; gadolinium enhancement showed concurrent tumor in the thoracic spinal cord from T10 to T11. Systemic survey identified a nodular mass in the lung that was verified as small-cell carcinoma. Following initial failed treatment by high-dose steroid, the patient underwent an emergent microsurgical tumor resection. Histological examination was identical with the lung carcinoma. The patient died of tumor progression at the 47th day after admission. At autopsy, only changes of edema were found in the gray matter of the cord, while tumor cells were not noted in it. Conclusion. Metastasis may rarely present symptoms of LETM. Prompt identification of underlying etiology by contrast examination and systemic survey is crucial for the patient assumed as LETM.